2014
DOI: 10.12998/wjcc.v2.i12.828
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disordered breathing in interstitial lung disease: A review

Abstract: Patients with interstitial lung disease commonly exhibit abnormal sleep architecture and increased sleep fragmentation on polysomnography. Fatigue is a frequent complaint, and it is likely that poor sleep quality is a significant contributor. A number of studies have shown that sleep disordered breathing is prevalent in this population, particularly in the idiopathic pulmonary fibrosis subgroup. The factors that predispose these patients to obstructive sleep apnoea are not well understood, however it is believ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 46 publications
1
19
1
Order By: Relevance
“…Diminished sleep quality has been linked to poor self‐reported health status in ILD patients . Our study confirmed previous findings of aberrant sleep architecture, noting in particular, reduced REM sleep, poor sleep efficiency and frequent arousals . Sleep fragmentation was in part related to desaturation and obstructive events.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Diminished sleep quality has been linked to poor self‐reported health status in ILD patients . Our study confirmed previous findings of aberrant sleep architecture, noting in particular, reduced REM sleep, poor sleep efficiency and frequent arousals . Sleep fragmentation was in part related to desaturation and obstructive events.…”
Section: Discussionsupporting
confidence: 90%
“…35,36 Our study confirmed previous findings of aberrant sleep architecture, noting in particular, reduced REM sleep, poor sleep efficiency and frequent arousals. 4,35,37,38 Sleep fragmentation was in part related to desaturation and obstructive events. Other likely contributing factors include nocturnal cough, pain, mood disturbance and treatment side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have linked increased mortality risk with the number of nocturnal desaturation events and nadir sleep oxygen saturation in ILD patients . Justifications for investigation and treatment of SDB in this population include the association between OSA and the development of PH, as well as the impact of sleep fragmentation on daytime functional status and quality of life . Standard screening questionnaires for the presence of SDB (such as the Epworth Sleepiness Scale) are poorly sensitive in IPF patients and thus identifying those at risk can be challenging .…”
Section: Sleep‐disordered Breathingmentioning
confidence: 99%
“…103,104 Justifications for investigation and treatment of SDB in this population include the association between OSA and the development of PH, as well as the impact of sleep fragmentation on daytime functional status and quality of life. [104][105][106][107][108] Standard screening questionnaires for the presence of SDB (such as the Epworth Sleepiness Scale) are poorly sensitive in IPF patients and thus identifying those at risk can be challenging. 93,103,109,110 In-laboratory polysomnography or home-based sleep studies may be considered in IPF patients for the detection of OSA and/or significant nocturnal hypoxaemia; however, the optimal timing of these investigations is unclear.…”
Section: Sleep-disordered Breathingmentioning
confidence: 99%
“…First of all, it is believed that restrictive lung diseases reduce upper airway tone, increasing collapsibility due to reduced caudal traction and that increased BMI can also contribute to the genesis of OSA. Also, alterations of ventilatory drive, frequent in IPF patients, are likely to play a role [Troy and Corte, 2014]. Last to be considered is the hypothesis that OSA, through mechanisms of oxidative stress, micro-aspiration from GER and insults due to mechanical traction, would create a chronic subclinical lung injury that, in susceptible individuals could open the door to IPF [Lederer et al 2012;Lee et al 2014 a].…”
Section: Osas In Ipfmentioning
confidence: 99%